THE PARTICIPATION OF IGIP IN THE 2014 WEEF - Michael E. Auer; Axel Zafoschnig (Высшее образование в России, 2016)
The paper describes the main achievements of the International Society for Engineering Pedagogy (IGIP) in the process of organization and participation in the 2014 World Engineering Education Forum. IGIP members were presenters at the plenary and numerous parallel sessions, participated in the IGIP Award ceremony.